Factors Affecting the Income of Capture Fishermen in Kenagarian Tiku V Jorong, Tanjung Mutiara District, Agam Regency, West Sumatra - Rahmah, Hadya Alifhia; Zulkarnaini, Zulkarnaini; Arief, Hazmi (Jurnal Perikanan dan Kelautan, 2025)
Tiku V Jorong is a marine coastal area where most of the population relies on the fisheries sector for their livelihood, particularly marine capture fisheries, which serve as their primary source of income. This research, conducted in February 2025, aims to analyze the factors influencing the income of shrimp capture fishermen in Jorong Muaro Putuih, Kenagarian Tiku V Jorong, Tanjung Mutiara District, Agam Regency, West Sumatra Province. The research method used is a quantitative approach with a survey of 25 respondents who are shrimp capture fishermen using gillnet fishing gear. The data were analyzed using multiple linear regression to examine the effect of independent variables, namely, operational costs, work experience, and catch volume, on the dependent variable, which is fishermen's income. The results of this study show that all three variables significantly affect fishermen's income. Catch volume and work experience have a positive influence, while operational costs have a negative effect on income